2019
DOI: 10.1093/dnares/dsz006
|View full text |Cite
|
Sign up to set email alerts
|

Developmental atlas of the RNA editome in Sus scrofa skeletal muscle

Abstract: Adenosine-to-inosine (A-to-I) RNA editing meditated by adenosine deaminases acting on RNA (ADARs) enzymes is a widespread post-transcriptional event in mammals. However, A-to-I editing in skeletal muscle remains poorly understood. By integrating strand-specific RNA-seq, whole genome bisulphite sequencing, and genome sequencing data, we comprehensively profiled the A-to-I editome in developing skeletal muscles across 27 prenatal and postnatal stages in pig, an important farm animal and biomedical model. We dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 61 publications
(84 reference statements)
10
31
0
Order By: Relevance
“…Previous studies suggested that A-to-I RNA editing might disturb the existing miRNA binding or generate novel miRNA binding [5,13,39]. The results of the present study showed that the A-to-I editing of 143 DESs might affect the binding ability of miRNA.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…Previous studies suggested that A-to-I RNA editing might disturb the existing miRNA binding or generate novel miRNA binding [5,13,39]. The results of the present study showed that the A-to-I editing of 143 DESs might affect the binding ability of miRNA.…”
Section: Discussionsupporting
confidence: 45%
“…The RNA editing sites in PG were identified using a previously published pipeline [13]. This pipeline was modified based on previous studies in other species [9,10,12,[25][26][27] and has been proved to be efficient and solid for the accurately identification of high-confidence RNA editing in pigs [13]. Briefly, the variants called by the transcriptome data were filtered by the following steps:…”
Section: Rna Editing Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings imply that SPPL2A, which participates in the immune response, may be specially activated through RNA editing mechanisms, when Gram-negative bacteria infect different types of tissues. Comparing our results with the atlas of the RNA editome in Sus scrofa skeletal muscle [78], we confirmed 22 of 57 RNA editing sites expressed in the endometrial tissues. Significant AAF changes in 3 UTR TMEM161A and upstream from GFM1 could be linked with the potential mechanism of implantation failure [79] and intrauterine growth retardation [80], respectively.…”
Section: Discussionsupporting
confidence: 75%